2022
DOI: 10.3390/brainsci12040430
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Confirmed Olfactory Bulb Reduction in Long COVID-19: Literature Review and Case Series

Abstract: An altered sense of smell and taste was recognized as one of the most characteristic symptoms of coronavirus infection disease (COVID-19). Despite most patients experiencing a complete functional resolution, there is a 21.3% prevalence of persistent alteration at 12 months after infection. To date, magnetic resonance imaging (MRI) findings in these patients have been variable and not clearly defined. We aimed to clarify radiological alterations of olfactory pathways in patients with long COVID-19 characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
0
28
0
3
Order By: Relevance
“…The release of pro-inflammatory cytokines and the activation of microglia reduce adult hippocampal neurogenesis, which, in turn, causes mood and cognitive disturbances typically observed in chronic inflammatory disorders ( Chesnokova et al, 2016 ). Damage to the olfactory bulb was demonstrated in long-COVID patients associated with long-term olfactory dysfunction ( Frosolini et al, 2022 ). This damage might extend to proximal and connected regions, affecting the limbic system and, consequently, impairing emotional and memory networks ( Díez-Cirarda et al, 2022 ; Goehringer et al, 2022 ; Kay, 2022 ; Martini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The release of pro-inflammatory cytokines and the activation of microglia reduce adult hippocampal neurogenesis, which, in turn, causes mood and cognitive disturbances typically observed in chronic inflammatory disorders ( Chesnokova et al, 2016 ). Damage to the olfactory bulb was demonstrated in long-COVID patients associated with long-term olfactory dysfunction ( Frosolini et al, 2022 ). This damage might extend to proximal and connected regions, affecting the limbic system and, consequently, impairing emotional and memory networks ( Díez-Cirarda et al, 2022 ; Goehringer et al, 2022 ; Kay, 2022 ; Martini et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 causes olfactory dysfunction in many patients, being reported by long-COVID patients as a frequent symptom (Doty, 2022). Some possible causes of olfactory dysfunction are olfactory cleft obstruction, olfactory bulb atrophy, inflammation, downregulation of olfactory receptor proteins, and massive activation of macrophages and release of cytokines (Keshavarz et al, 2021;Xydakis et al, 2021;Frosolini et al, 2022). The virus can enter the olfactory bulbs and affect the brain through transcribriform or vascular routes (Brann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This post-viral OD covers 40% of cases; in fact, the loss of olfactory abilities is certainly one of the symptoms that is most frequently found in affected subjects (about 87% of patients who develop COVID-19 in mild or moderate symptomatology), much higher numbers than the previous coronaviruses, which instead counted a few patients with the same dysfunction [ 56 ]. In addition, magnetic resonance studies conducted on affected and anosmic patients have reported changes in the olfactory bulb and in the structures responsible for olfactory perception [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, magnetic resonance imaging performed before and after COVID-19 infection has shown significant changes in experimental subjects’ brain structure compared to controls [ 10 ]. In particular, it seems that COVID-19 can cause a reduction in gray matter thickness in the orbitofrontal cortex and the parahippocampal gyrus and increased injury signs in brain areas that are functionally related to the primary olfactory cortex [ 11 ].…”
Section: Introductionmentioning
confidence: 99%